ISLAMIC BANKING PROFITABILITY AND THE ROLE PLAYED BY THE PHILIPPINE ECONOMY: A VECTOR AUTOREGRESSION (VAR) MODEL APPROACH - Sali, Najeeb Razul A.; Hawariyuni, Weni; Zulfikri, Zulfikri; Sahim-Salid, Halima A. (I-iECONS e-proceedings, 2023)
This study presents the rise and fall of Islamic banking in the Philippines and the role the economy plays as reflected in its economic history. It used econometric analysis of the past financial data of both Islamic banking as proxied by its Return on Asset (ROA) values and its host economy proxied by inflation, population, and the Gross Domestic Product or the real GDP. With EViews10 software used to perform the ADF Dickey-Fuller stationarity test, Johansen Cointegration tests the Vector Autoregressive (VAR) model, and it found that there was a short-run relationship between the economy and Islamic banking in the country. Granger causality test ascertained that the association found was unidirectional, running only from the economy to Islamic banking and that there was not enough evidence to show the reverse causal effect from the latter to the former. The impulse response function found that economic growth is positively associated with the Islamic banks’ profitability in the country, while changes in the bank’s profitability do not impact the economy. This study concludes that the Philippine economy plays a major role in Islamic banking profitability, while the same cannot be said the other way around.